(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The article describes the system of CLIL and its use briefly. The paper describes the origin, kinds and needs of CLIL. Next, it deals with details of CLIL, potential benefits. Also listed are the competence and educational standards for teachers. This study aimed at investigating the effectiveness of using the CLIL approach to develop student teachers’ oral communicative skills.